Regional Citrate Anticoagulation for High Volume Continuous Venovenous Hemodialysis in Surgical Patients With High Bleeding Risk. Issue 2 (29th August 2012) - Kalb, Robert; Kram, Rainer; Morgera, Stanislao; Slowinski, Torsten; Kindgen‐Milles, Detlef
Abstract Acute kidney injury requiring renal replacement therapy occurs in up to 10% of all intensive care unit patients. Those who are hemodynamically unstable are often treated with continuous renal replacement therapy requiring continuous anticoagulation of the extracorporeal circuit. This is usually achieved by infusion of unfractionated heparin, which subsequently increases the risk of bleeding. To avoid systemic anticoagulation for continuous renal replacement therapy, regional anticoagulation with citrate has been introduced. We studied safety and efficacy of regional citrate anticoagulation for continuous venovenous hemodialysis in surgical patients requiring high dialysis doses. This was an observational prospective study in a 40‐bed surgical intensive care unit at a university hospital. During a 12‐month study period, all consecutive critically ill patients with high risk of bleeding requiring continuous renal replacement therapy continuous renal replacement therapy were treated with citrate anticoagulation for continuous venovenous hemodialysis. Prescribed dialysis dose was 45 mL/kg per h with a 10% increase for expected downtime. We studied filter lifetime, delivered dialysis dose, control of acid–base status, bleeding episodes, and adverse effects, that is, citrate intolerance. The total number of filters analyzed in 75 patients was 100. Mean (± standard deviation) filter running time was 78 ± 25 h. Fifty‐one circuits had to be renewed because of extended filter running time (96 ± 18 h), 33 discontinued for reasons not related to renal replacement therapy (62 ± 19 h), and 13 due to filter clotting (58 ± 18 h). The mean dialysis dose during the first 72 h was 49 ± 14 mL/kg per h. Overall, acid–base status after 72 h was well controlled in 62% of patients, metabolic alkalosis (pH > 7.45) occurred in 29%, and metabolic acidosis (pH < 7.35) in 9%. In one patient, treatment was stopped because of citrate accumulation. Citrate intoxication or overt bleeding episodes were not observed. Regional citrate anticoagulation for continuous venovenous hemodialysis is a safe and effective method to deliver a high dialysis dose in critically ill patients with a high risk of bleeding. Filter patency was excellent, acid–base status was well controlled, and clinically relevant adverse effects were not observed. Therefore, citrate anticoagulated continuous venovenous hemodialysis is a useful treatment option for patients with acute kidney injury requiring high dialysis doses and at risk of bleeding.